A new cynodont record from the Tropidostoma Assemblage Zone of the Beaufort Group: implications for the early evolution of cynodonts in South Africa - Botha-Brink, J.; Abdala, F. (Bernard Price Institute for Palaeontological Research, University of the Witwatersrand, 2008)
A new specimen of cynodont has been recovered from the lower Upper Permian levels of the Tropidostoma Assemblage Zone of the South African Karoo Basin. A series of characters, including the presence of an interpterygoid opening, triconodont postcanine teeth, which are circular in crown view, a probable lingual cingulum, and most significantly, the presence of a masseteric fossa high on the coronoid process, allows this specimen to be assigned to the Procynosuchidae. However, unlike most procynosuchids, precanine teeth are absent and the incisors are represented by four left and five right upper and probably, three lower teeth. Considering the small size of the new specimen from the Tropidostoma Assemblage Zone we identify it as a juvenile Procynosuchus delaharpeae, the only species currently recognized in the genus. The low number of incisors and absence of precanines in this specimen are interpreted as ontogenetic variation (i.e. juvenile characters). This discovery extends the biostratigraphic range of Procynosuchus, as it is now recorded in three assemblage zones, indicating that this taxon is the longest-lived cynodont in the Karoo Basin. The new specimen of Procynosuchus and the recently described Charassognathus gracilis, are the oldest global records of cynodonts, and indicate an earlier initial radiation of this lineage than was previously thought.
Keywords: Procynosuchus; Cynodontia; South Africa; biostratigraphy; Late Permian